Evaluating the standards for solar PV installations in the Iberian Peninsula: Analysis of tilt angles and determination of solar climate zones. (February 2022) - González-González, E.; Martín-Jiménez, J.; Sánchez-Aparicio, M.; Del Pozo, S.; Lagüela, S.
Highlights: Determination of the optimal tilt angle for PV panels in the Iberian Peninsula. Evaluation of optimal tilt angle equations for PV panels. Updated climate zoning based on solar irradiation for the Iberian Peninsula. Energy losses are calculated per unit angle regarding optimal tilt angle. Abstract: One of the main factors for the determination of the energy yield of photovoltaic (PV) systems is the incoming solar irradiation, which is a function of (i) the spatial configuration of the PV panels with respect to the Sun for (ii) each location. The aim of this work is to determine the PV potential in the Iberian Peninsula, attending to the two main criteria. Regarding (i), different methods for the estimation of the optimal PV tilt angle in the Iberian Peninsula, and how this parameter influences the PV production, are analysed. With respect to (ii), a climate zoning is proposed for the Iberian Peninsula, to be used as reference for the estimation of solar radiation for each location. The study is performed using experimental data from capital cities of the Iberian Peninsula (Spain and Portugal). In addition, the annual PV production was compared for several tilt angle configurations in order to estimate the energy losses per unit angle with respect to the energy produced with the optimal tilt angle. Results show that the tilt angle can be fixed as 34° for all the Iberian Peninsula, being the annual PV production losses lower than 1%. Differences lower than 1% were obtained between the different approaches existing in literature to calculate the optimal tilt angle, showing that although the tilt angle is a key parameter that influences the PV energy production, its variation must be significant in order to have an impact on production losses.